Performance analysis of low-complexity welch power spectral density for automatic frequency analyser - Teh Yi Jun; Asral Bahari Jambek; Uda Hashim (Bulletin of Electrical Engineering and Informatics, 2019)
The aim of this paper is to investigate the performance of the Low Complexity Welch Power Spectral Density Computation (PSDC). This algorithm is an improvement from Welch PSDC method to reduce the computational complexity of the method. The effect of the sampling rate and the input frequency toward to accuracy of frequency detection is being evaluated. From the experiment results, sampling rate nearest to the twice of the input frequency provides the highest accuracy which achieved 99%. The ability of the algorithm to perform complex signal also has been investigated.